PENGARUH LEVERAGE, LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN, CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Manufaktur Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Dipateruna Teruna Awaludin; Eka Rahmawati (JURNAL REKAYASA INFORMASI, 2022)
Abstraks This study aims to examine several factors that can influence tax aggressiveness, namely leverage, liquidity, profitability, company size, capital intensity. The population used in this study were all goods and consumer sector manufacturing companies listed on the Indonesian Stock Exchange (BEI) in 2015-2019. The sample selection used purposive sampling. Based on the criteria, 30 companies were selected as samples in this study. The analytical tools used are normality test, classic assumption test, multiple linear regression test, model test and hypothesis test. The results showed that profitability, firm size affect tax aggressiveness. Meanwhile, Leverage, Liquidity, and Capital Intensity have no effect on tax aggressiveness. Key Word : Leverage, Liquidity, Profitability, Capital Intencity, Tax Aggressiveness Company Size,